Business Management for the IB diploma study and revision guide - Hoang, Paul (Hodder Education Group, 2016)
This Study and Revision Guide will ensure you approach your exams feeling confident and prepared through the help of accurate and accessible notes, examiner advice, and exam-style questions on each key topic : Practise and check your understanding on a range of Exam Practice questions; Be aware of the essential points with key terms and facts for each topic; Discover what you need to achieve certain grades with advice and tips, including common mistakes to avoid.